2015
DOI: 10.1002/ana.24472
|View full text |Cite
|
Sign up to set email alerts
|

Proportional recovery after stroke depends on corticomotor integrity

Abstract: These findings indicate that upper limb impairment resolves by 70% of the maximum possible, regardless of initial impairment, but only for patients with intact corticomotor function. Impairment resolution seems to reflect spontaneous neurobiological processes that involve the ipsilesional corticomotor pathway. A better understanding of these mechanisms could lead to interventions that increase resolution of impairment above 70%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
429
5
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(466 citation statements)
references
References 49 publications
28
429
5
4
Order By: Relevance
“…Our findings agree with earlier studies on the modulation of CSE after stroke [3,31]. The rMTs of the UH corresponded well with those reported in the healthy population [28] and agree with earlier reports in stroke patients, which demonstrate that in general the CSE of the contralesional corticospinal tract is within normal limits in the acute and chronic stages [2,30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings agree with earlier studies on the modulation of CSE after stroke [3,31]. The rMTs of the UH corresponded well with those reported in the healthy population [28] and agree with earlier reports in stroke patients, which demonstrate that in general the CSE of the contralesional corticospinal tract is within normal limits in the acute and chronic stages [2,30].…”
Section: Discussionsupporting
confidence: 93%
“…The changes in CSE tend to be observed on the affected hemisphere (AH), while the CSE on the contralesional unaffected hemisphere (UH) is often less altered [3,4,30]. This interhemispheric asymmetry has been reported to be greatest in the acute stage, after which it begins to recover [3,30]. Recovery from stroke is based at least partly on the reorganization of the surviving parts of the brain and rebuilding of functional networks [23,26].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with a recent study 6 and extends previous algorithms for prediction of the severity of impairment at the chronic stage 7 to prediction of improvement gains. Patients with mild degeneration observed in the CST will recover about 70% of impaired upper limb function, while expected recovery in patients with severe CST degeneration drops to approximately ,30%.…”
supporting
confidence: 92%
“…9 In line with this concept, Byblow et al 10 recently demonstrated that CST integrity as assessed by the presence of motor-evoked potentials (MEPs) was a better predictor of the ability to recover compared with initial clinical impairment, thus improving the 70% rule. Furthermore, they also demonstrated the added value of fractional anisotropy (FA) measurements in the CST toward improving prediction of motor function recovery in combination with MEPs.…”
Section: April 2016mentioning
confidence: 96%